Elbow Ulnar Collateral Ligament Shoelace Repair with Internal Bracing for Treating Throwing Athletes Who Have Ulnar Collateral Ligament Instability - Uchida, Soshi (Arthrosc Tech, 2021)
This Technical Note aimed to present a surgical technique of ulnar collateral ligament (UCL) shoelace repair using suture anchors and double suture tapes in combination with internal bracing to correct UCL instability along with epiphyseal avulsion of the medial epicondyle in throwing athletes Skeletally immature throwing athletes playing baseball and softball are at a risk of sustaining medial epicondyle epiphyseal separation that can result in UCL instability, predisposing to elbow UCL disruption later. There are several surgical techniques that can restore elbow UCL function and stability. In cases where large fragments of the medial epicondyle are present in skeletally immature athletes, the residual bony fragment and the shortened, chronically injured UCL make surgical treatment quite challenging. Recent studies have shown that UCL repair with internal bracing can effectively treat acute UCL injury. However, this procedure is not ideal for restoring large disruption of the UCL such as fragmentation. Here, we present a surgical technique of UCL shoelace repair using suture anchors with double suture tapes in combination with internal bracing for correcting UCL instability concurrent with epiphyseal fragmentation of medial epicondyle in throwing athletes.